2008
DOI: 10.1111/j.1750-3841.2008.00956.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and Pulsed Electric Field Treatments Have Additive Effect on Inactivation of E. coli in Apple Juice

Abstract: Apple juice inoculated with Escherichia coli ATCC 23472 was processed continuously using either ultraviolet (UV), high-voltage pulsed electric field (PEF), or a combination of the PEF and UV treatment systems. Apple juice was pumped through either of the systems at 3 flow rates (8, 14, and 20 mL/min). E. coli was reduced by 3.46 log CFU/mL when exposed in a 50 cm length of UV treatment chamber at 8 mL/min (2.94 s treatment time with a product temperature increase of 13 degrees C). E. coli inactivation of 4.87 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 37 publications
3
26
5
Order By: Relevance
“…However, few studies have compared the efficacy of hurdle combinations of novel preservation technologies against traditional methods (Caminiti et al, 2010;Gachovska, Kumar, Thippareddi, Subbiah, & Williams, 2008;Noci, Walkling-Ribeiro, Cronin, Morgan, & Lyng, 2009). The present study compared the effects of two technologies, PEF and MTS, when applied under selected conditions, either individually or in combination (PEF þ MTS and its reverse) on microbial inactivation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, few studies have compared the efficacy of hurdle combinations of novel preservation technologies against traditional methods (Caminiti et al, 2010;Gachovska, Kumar, Thippareddi, Subbiah, & Williams, 2008;Noci, Walkling-Ribeiro, Cronin, Morgan, & Lyng, 2009). The present study compared the effects of two technologies, PEF and MTS, when applied under selected conditions, either individually or in combination (PEF þ MTS and its reverse) on microbial inactivation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the sequence order had no significant effect on microbial inactivation (log reductions of 2.3 and 2.25 for PEF þ TS and TS þ PEF, respectively). Gachovska et al (2008) observed an additive effect on E. coli in apple juice when treated by a combination of PEF (60 kV/cm, 11.3 pulses) and UV processing (exposure for 1.8 s in a 30 cm length chamber). Also, Noci et al (2008) reported an additive effect on the inactivation of native microbiota in freshly squeezed apple juice when a batch UV pretreatment was followed by PEF at 40 kV/cm.…”
Section: Application Of Paired Non-thermal Hurdlesmentioning
confidence: 91%
“…Geveke (2005b) found that L. innocua exhibited a higher degree of resistance to UV light than E. coli. Different flow rates (8, 14 and 20 ml/min) and lengths of UV treatment chamber (30, 40 and 50 cm) were tested by Gachovska et al (2008), who achieved a reduction of 3.46 log cfu/ml for E. coli in apple juice when exposed in a 50-cm length of UV treatment chamber at 8 ml/min. Ngadi et al (2003) Results are expressed as log cfu/ ml TSA tryptone soya agar medium, LSA listeria selective agar medium, EMB eosin-methylene blue medium, ND counts were below limit of detection investigated the effect of pH (3.5 and 9.1), depth of food medium (1, 3.5, 5 and 10 mm) and UV light dosage (0 to 0.39 J/cm 2 ) on E. coli inactivation in apple juice and liquid egg white.…”
Section: Microbial Countsmentioning
confidence: 99%
“…The application of ultraviolet C light (UV-C, 200-280 nm) was successfully used to inactivate microorganisms in water and various types of liquid foods and beverages, such as fruit juices, soft drinks, beer and wine [4,12,16,17,[24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%